Chinese yam mucus freeze-dried powder, Chinese yam microgel and preparation method and application thereof

By preparing yam mucus lyophilized powder and hydrogel, the problems of stopping bleeding and repair of traumatic injuries are solved, and the effect of accelerating wound healing is achieved.

CN119792428APending Publication Date: 2025-04-11THE SECOND AFFILIATED HOSPITAL TO NANCHANG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411849959.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problems of traumatic injuries, especially severe bleeding and skin defects.

Method used

Yam mucus was obtained by peeling, juicing and filtering the yam, and lyophilized powder was prepared by low-temperature freezing and vacuum freeze-drying methods, and then hydrating the yam microgel was prepared for trauma hemostasis and repair.

Benefits of technology

Yam microgels are non-cytotoxic and can enhance cell proliferation, promote neovascularization, regulate inflammatory responses, thereby accelerating wound healing for traumatic injuries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119792428A_ABST
    Figure CN119792428A_ABST
Patent Text Reader

Abstract

The invention provides Chinese yam mucus freeze-dried powder, Chinese yam microgel and a preparation method and application of the Chinese yam mucus freeze-dried powder and the Chinese yam microgel, and belongs to the technical field of medical medicines. The Chinese yam mucus freeze-dried powder is prepared by juicing Chinese yam, filtering to obtain Chinese yam mucus, freezing at low temperature, and freeze-drying in vacuum. The Chinese yam microgel formed by hydration of the Chinese yam mucus freeze-dried powder has a good wound hemostasis effect and a good traumatic injury repair effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of medical technology, and in particular to yam mucus freeze-dried powder, yam microgel, and preparation methods and applications thereof. Background Art

[0002] Trauma is a leading cause of disease and death worldwide, with millions of cases reported each year. The most critical consequences of traumatic injury include severe bleeding and skin loss, especially in cases involving road traffic accidents, industrial accidents and violent incidents. After the bleeding is controlled, attention must also be paid to the repair of damaged skin tissue. Summary of the invention

[0003] Based on this, it is necessary to provide a yam mucus freeze-dried powder, yam microgel and its preparation method and application, which can be used for trauma hemostasis and repair.

[0004] The present invention adopts the following technical solution:

[0005] The present invention provides a yam mucus freeze-dried powder, and the preparation method of the yam mucus freeze-dried powder comprises: peeling the yam, squeezing the juice, filtering the yam to obtain the yam mucus, freezing at low temperature, and vacuum freeze drying. The temperature of the low temperature freezing is -80 to -40°C; the temperature of the vacuum freeze drying is -80 to -40°C.

[0006] In some of the embodiments, the yam is iron stick yam.

[0007] The present invention can also provide a yam microgel, which is prepared by hydrating yam mucus freeze-dried powder. Preferably, the weight ratio of yam mucus freeze-dried powder to water in the hydration process is (10-1) 1:1.

[0008] The invention also provides application of yam mucus freeze-dried powder and yam microgel in preparing hemostatic products.

[0009] In some embodiments, the hemostatic product is an in vivo hemostatic product or a surface hemostatic product.

[0010] The present invention also provides the use of yam mucus freeze-dried powder and yam microgel in preparing products for repairing traumatic injuries.

[0011] Compared with the prior art, the core advantages of the present invention are:

[0012] The present invention has found through a large number of experiments that yam mucus freeze-dried powder and yam microgel can be used for wound hemostasis and repair. Yam microgel has no cytotoxicity, can enhance cell proliferation, help new blood vessel formation and regulate inflammatory response, and help accelerate wound healing of traumatic injuries. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The preparation and characterization of yam microgel; Figure A shows the preparation process of yam microgel, including peeling, grinding, juicing, screening, low-temperature freezing and vacuum freeze-drying (EXTRACTION, Freeze-drying, Gelling); Figure B shows photos of yam freeze-dried powder selected by mesh sieves with different particle sizes (#20, #40, #80, #100, #200, #300) and the corresponding internal structure of yam microgel; Figures C and D are the statistical results of the rheological properties of yam microgel under concentration; Figures E and F are the statistical results of the shear strength (Shear Strength) of yam microgel made from yam freeze-dried powder with different particle sizes (#20, #40, #80, #100, #200, #300).

[0014] Figure 2 The results of the biocompatibility test of yam microgels; Figures A and B show the proliferation of fibroblasts treated with yam microgels of different concentrations (BLANK, 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL) for 1, 3 and 5 days; Figures C and D show the anti-radical efficiency of yam microgels of different concentrations (BLANK, 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL) officiency) results; Figures E and F are the wound scratch test results of HUVECs treated with yam microgels of different concentrations (BLANK / Control, 0.1mg / mL, 0.5mg / mL, 1mg / mL, 2mg / mL, 3mg / mL) for 12h and 24h; Figures G and H are the blood compatibility test results of yam microgels of different concentrations (0.1mg / mL, 0.5mg / mL, 1mg / mL, 2mg / mL, 3mg / mL from left to right) and positive control (Posltive); Figures I and J are the statistical results of the biodegradation rate of yam microgel (YAM) within 8 weeks (1w, 2w, 4w, 8w).

[0015] Figure 3 The figures are the test results of the in vitro hemostatic ability of yam microgel; wherein, Figures AC show the adsorption capacity of yam microgel, gelatin sponge and gauze on red blood cells; Figures D and E are the statistical results of blood clotting time at yam microgel concentrations of 1 mg / mL, 2 mg / mL and 3 mg / mL, respectively; Figure F uses SEM images to show the adsorption behavior of microgel on platelets and red blood cells, with gelatin sponge and gauze as positive controls.

[0016] Figure 4 The figures are the results of the in vivo hemostatic ability test of yam microgel; wherein, Figure A is a photograph of the hemostatic ability of yam microgel, gauze and gelatin sponge in the rat tail-cut bleeding model; Figures B and C are the quantitative analysis results of the hemostatic time and total blood loss of yam microgel, gauze and gelatin sponge in the rat tail-cut bleeding model; Figure D is the hemostatic ability of yam microgel, gauze and gelatin sponge in the rat liver perforation bleeding model; Figures E and F are the quantitative analysis results of the hemostatic time and total blood loss (Total blood loss) of yam microgel, gauze and gelatin sponge in the rat liver perforation bleeding model; Figures G and H are the application of yam microgel to stop liver bleeding and the interface between the liver and the microgel after hemostasis; Figures I and J are the application of yam microgel to stop heart bleeding and the interface between the heart and the microgel after hemostasis.

[0017] Figure 5 The results of the application test of yam microgel in acute skin wound regeneration are shown in Figure A. Figure A is a schematic diagram of acute skin wound treatment. Figure B is a photo of wounds treated with or without yam microgel after 3, 7 and 14 days. Figure C is the statistical results of the healing rate of wounds treated with or without yam microgel at 7 and 14 days. Figure D is the H&E staining results of the central area of ​​wounds treated with or without yam microgel at 3 and 7 days. Figure E is the re-epithelialization rate of wounds at 7 and 14 days. Figure F shows the results of Masson trichrome staining of the central area of ​​the wound treated or not with yam microgel at 3 and 7 days; Figures G and H show the expression results of K6 at the edge and center of the wound after 7 and 14 days; Figures I and J show the expression results of Ki-67 at the edge and center of the wound after 7 and 14 days; Figures K and L show the expression results of CD31 at the edge and center of the wound after 7 and 14 days; Figures M and N show the expression results of α-SMA at the edge and center of the wound after 7 and 14 days.

[0018] Figure 6The figures are the test results of inflammatory response induced by yam microgel in the process of wound healing; wherein, Figure A and Figure B are the expression results of CD45 leukocyte markers in the wound center after 3 days and 7 days with or without yam microgel; Figure C and Figure D are the expression results of Ly6G monocyte, granulocyte and neutrophil markers in the wound center after 3 days and 7 days with or without yam microgel; Figure E and Figure F are the markers of CCR7M1 macrophages and CD206M2 macrophages in the wound center after 3 days and 7 days with or without yam microgel; Figure G and Figure H are the expression; Figure I is the ratio of the number of M2 and M1 macrophages in wounds treated with yam microgel or without yam microgel for 3 days and 7 days; Figure J is a schematic diagram of yam microgel promoting the polarization of M2 macrophages.

[0019] Figure 7 The figures are the test results of the application of yam microgel in wound suture; Figure A is a schematic diagram of skin scratch treatment, and suture (Suture) and cyanoacrylate glue (Cyanoacrylate glue) are positive controls; Figure B is photos of skin scratches treated with suture, cyanoacrylate glue and yam microgel after 3, 5 and 7 days; Figures C and D are the expressions of α-SMA at the scratches of the suture group, cyanoacrylate group and yam microgel group on the 7th day; Figures E and F are the expressions of K6 at the scratches of the suture group, cyanoacrylate group and yam microgel group on the 7th day; Figures G and H are the expressions of Ki67 at the scratches of the suture group, cyanoacrylate group and yam microgel group on the 7th day; Figures I and J are the expressions of CD31 at the scratches of the suture group, cyanoacrylate group and yam microgel group on the 7th day. DETAILED DESCRIPTION

[0020] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly. The following embodiments are only used to illustrate the present invention, but are not only used to limit the scope of the present invention. Based on the specific embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the protection scope of the present invention. In the embodiments of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art; in the embodiments of the present invention, if not specifically specified, the technical means used are conventional means well known to those skilled in the art.

[0021] Animal experiments were approved by the Animal Ethics and Welfare Center of Nanchang University (NCULAE-20221031129). All rats were purchased from Ganzhou Animal Husbandry Bureau Tianqin Biotechnology Co., Ltd. The Chinese yam used in the experiment was purchased from a supermarket. Gelfoam was purchased from Quick Health Medical Technology (catalog number: 2640494, Guangzhou, China). Dulbecco's modified Eagle medium (DMEM, catalog number: 11965118), penicillin and streptomycin antibiotics (PS, catalog number: 15140122), and fetal bovine serum (FBS, catalog number: 10099-141C) were all from Invitrogen, USA. Various antibodies, including anti-CD206 rabbit pAb (catalog number: PA5-101657), anti-CD31 rabbit polyclonal antibody (catalog number: ab28364), anti-CD45 rabbit pAb (catalog number: ab10558 ab10558), anti-CD68 rabbit pAb (catalog number: ab283654), anti-Ki67 rabbit pAb (catalog number: ab16667) and anti-CCR7 rabbit pAb (catalog number: ab253187) were purchased from Abcam (Cambridge, UK). Anti-K6 rabbit pAb (catalog number: bsm-60235R) was purchased from Bioss (Beijing, China), and anti-Ly6G (catalog number: 551459) was purchased from BD Pharmingen. Cell counting kit-8 (CCK-8, catalog number: C0040) was purchased from Bio-Tianmei Biotechnology (Shanghai) Co., Ltd. Acridine staining / ethylenediamine bromide staining kit (Catalog number: M247364) was purchased from Mindray Technology (Shenzhen) Co., Ltd. Sodium citrate (Catalog number: C38585) and paraformaldehyde (Catalog number: 30525-89-4) were ordered from Aladdin (Shanghai, China). Calcium chloride (Catalog number: 012316) and glutaraldehyde (Catalog number: A17876) were from Alfa Aesar Chemical (Shanghai, China). Ethanol (Catalog number: 10009228, Beijing, China) was from Sinopharm Chemical. Hematoxylin-eosin staining kit (Catalog number: ZY61872FA) was provided by Zeyan Biotechnology Co., Ltd. (Shanghai, China).

[0022] Example 1

[0023] This example explores the preparation method of yam mucus freeze-dried powder, comprising the following steps:

[0024] The yam (variety: iron stick yam) is peeled, ground and juiced to obtain a yam extract; the yam extract is filtered (also called sieving) to obtain yam mucus, which is frozen at -80°C overnight (duration: 12 hours), and then vacuum-frozen (temperature: -80 to -40°C, duration: 12 hours) to obtain yam mucus freeze-dried powder.

[0025] The embodiment also explores the preparation of yam microgel, including the following steps: mixing yam mucus freeze-dried powder and water in a mass ratio of 1:1, freezing at -80°C overnight, vacuum freeze drying (temperature: -80 to -40°C, duration: 12h), and hydrogen peroxide plasma sterilization to form freeze-dried yam microgel.

[0026] Furthermore, the exploration process of this embodiment also conducted statistical analysis on the influence of the number of screening meshes on the yam mucus, including 20 mesh (#20), 40 mesh (#40), 80 mesh (#80), 100 mesh (#100), 200 mesh (#200) and 300 mesh (#300).

[0027] Morphological observation and testing

[0028] The morphology of the freeze-dried yam microgel and yam freeze-dried powder prepared in Example 1 was analyzed by scanning electron microscopy (SEM). The rheological properties were evaluated using a rheometer. In the strain-scanning test, the applied strain was adjusted in the range of 0.1% to 1000%, the angular velocity was kept constant at 10 rad / s, and the temperature was controlled at 25°C.

[0029] Adhesion properties test

[0030] The adhesive properties of the yam microgel prepared in Example 1 were evaluated using a standard tensile testing instrument and compared with the performance of commercial adhesives on pig skin. Fresh pig skin tissue was obtained from commercial sources, and the hair and fat on the tissue were removed before testing. The pig skin was cut into rectangles of 100 mm × 20 mm, and the adhesive overlap area was 20 mm × 20 mm. Yam microgels of different mesh sizes (#20, #40, #80, #100, #200, #300) were prepared at a concentration of 1 g / mL and mixed with water to form a yam hydrogel preparation. About 200 μL of the yam hydrogel preparation was evenly applied to the pig's skin. The shear adhesion strength was evaluated using a universal tensile testing device at a speed of 0.5 mm / s, and each test was repeated three times.

[0031] Cytotoxicity assay

[0032] In order to evaluate the effects of the yam mucus freeze-dried powder and yam microgel prepared in Example 1 on cell survival and proliferation, CCK-8 cell proliferation test and calcein AM / PI double staining test were performed. The specific steps are:

[0033] When performing the CCK-8 assay, L929 cells [L929 mouse connective tissue cells cultured in DMEM containing 10% FBS and 1% PS (37°C, 5% CO2)] were seeded in a 96-well plate at a number of 2000 cells / well and cultured at 37°C, 5% CO2 for 24 hours. Then, the growth medium was replaced with yam microgels on days 1, 3, and 5. CCK-8 reagent was added to each well and cultured at 37°C for 2 hours. The absorbance at 450nm was measured using an ELISA reader (n=4).

[0034] To assess cell viability using Calcein AM / PI staining, 10,000 L929 cells were seeded per well in a 24-well plate and cultured for 24 hours. The culture medium was then replaced with yam microgels and the cells were cultured for another 1 or 3 days. The cells were stained with Calcein AM / PI for 30 minutes and then immediately observed for cell viability using a fluorescence microscope.

[0035] Cell antioxidant assay

[0036] RAW264.7 cells were seeded into 24-well plates at a concentration of 20,000 cells / mL and cultured for 24 hours. The cells were then treated with different concentrations of yam microgels for 24 hours. Then, hydrogen peroxide (H2O2) was added to the culture medium and the final concentration was adjusted to 100 μmol / L. Subsequently, the cells were cultured for 30 minutes. The probe DCFH-DA (10 μmol / L) was used to stain the cells at 37°C and 5% CO2 for 30 minutes. The cells were rinsed three times with PBS before being observed under an inverted fluorescence microscope.

[0037] The calculation formula of clearance rate is as follows:

[0038] Clearance rate (%) = (1-ODsample / ODcontrol) x 100%.

[0039] Cell migration assay

[0040] HUVECs were seeded into 6-well plates to form a confluent monolayer. After the monolayer was formed, a wound was made using a 100 μL pipette tip. The cells were cultured in serum-free medium with different concentrations of yam microgels for 12 and 24 hours. The wound healing rate was determined using the following formula:

[0041] Wound healing rate (%) = (S0-St) / S0×100%,

[0042] Among them, S0 represents the wound area at 0 hours, and St represents the wound area at a specific time point.

[0043] Hemolysis test

[0044] The whole blood of the collected rats was centrifuged at 3000 rpm for 5 minutes to obtain the supernatant. The red blood cells were rinsed three times with PBS buffer (pH 7.4) to prepare a 5% red blood cell suspension. The yam mucus freeze-dried powder was ground in liquid nitrogen to prepare a hydrogel dispersion (0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL). 0.5 ml of aerogel and 0.5 ml of red blood cells were placed in a 1.5 ml test tube, placed at 37°C for 1 hour, and centrifuged for 10 minutes. The supernatant was transferred to a 96-well tube and A562 was measured. nm Absorbance. Deionized water (+), PBS (-). Hemolysis rate calculation formula:

[0045] Hemolysis rate (%)=(ODs-ODp) / (ODh-ODp)×100%,

[0046] Wherein, ODs, ODp and ODh represent the absorbance values ​​of sample, PBS buffer and deionized water, respectively.

[0047] Biodegradation test

[0048] The biodegradation of yam hydrogel was evaluated by subcutaneous implantation test. Rats were anesthetized with 3% sodium pentobarbital, and then 0.4mL of yam hydrogel (1g / mL) or gelatin was implanted into the back of the rats. The rats were killed at 1, 2, 4 and 8 weeks, and tissue samples in direct contact with the yam hydrogel were collected. The samples were fixed with 2.5% glutaraldehyde, embedded in paraffin, and sliced ​​at 5μm. Hematoxylin and eosin (H&E) staining was performed to analyze any inflammatory response and evaluate the biocompatibility and potential adverse effects of yam hydrogel.

[0049] Coagulation time test

[0050] The yam hydrogel, gelatin and gauze (5 mg per piece of gauze) were placed at the bottom of a 24-well plate. Mouse whole blood was mixed with 3.8% (weight percentage) sodium citrate (1:9, v / v). 1.26 mL of citrated blood was placed in a 4.5 mL Eppendorf tube and 0.14 mL of 0.1 M calcium chloride solution was added. The mixture was vortexed for 10 seconds, and then 50 μL of the solution was added to each well of the 24-well plate in turn, and each well was kept undisturbed during the coagulation process to observe the coagulation time. At 30 seconds, 1 minute, 2 minutes, 3 minutes, 4 minutes and 5 minutes, each well was rinsed with standard saline to stop the coagulation process. Continue rinsing until all soluble components in the blood are removed and the solution becomes clear. Sterile water was then added to each well and the color of the solution was observed. Finally, the absorbance value of the solution was measured to evaluate the results.

[0051] Interface reaction test of hemostatic materials

[0052] PRP (Chinese: platelet-rich plasma) was applied to the surface of yam hydrogel, gelatin and gauze (5 mg per piece of gauze) and incubated at 37°C for 1 hour. Afterwards, the dried samples were analyzed using a scanning electron microscope.

[0053] In the whole blood experiment, 50 μL of whole blood was placed on the surface of yam mucus freeze-dried powder, gauze and gelatin sponge, and incubated at 37°C for 30s, 1min, 2min, 3min, 4min and 5min, respectively. After the incubation, the samples were rinsed three times with PBS buffer, fixed with 2.5% glutaraldehyde for 2.5 hours, and then gradually dehydrated with ethanol. The dried samples were examined by scanning electron microscopy.

[0054] In vivo hemostasis assay

[0055] The hemostatic properties of yam mucus freeze-dried powder were evaluated using three different bleeding models: rat tail amputation model, liver puncture model, and spontaneous cardiac bleeding model. All animal experiments in this study were strictly reviewed and approved by the Animal Ethics and Welfare Center of Nanchang University (NCULAE-20221031129).

[0056] In the rat tail bleeding study, the rats were divided into four groups, three in each group. After 3% sodium pentobarbital anesthesia, pre-weighed filter paper was placed on the rat's tail. The rat's tail was cut 3 cm from the base, and pre-weighed gauze, gelatin sponge, and yam mucus freeze-dried powder were placed on the wound. The bleeding rate and duration were recorded. No hemostatic treatment was performed in the control group.

[0057] In the rat liver perforation bleeding model, the rats were divided into four groups, three in each group. After anesthesia, the liver was exposed. A hole was made in the liver. Gauze, sponge and yam powder were applied. Untreated rats were used as controls, and the bleeding volume and time were recorded.

[0058] In the rat cardiac bleeding model, rats were divided into groups and anesthetized. The rat hearts were exposed and punctured. Pre-weighed gauze, sponges, and yam mucus freeze-dried powder were applied to the wounds, and untreated rats were used as controls. Bleeding data were recorded. Samples were processed and examined with a scanning electron microscope.

[0059] Rats were anesthetized with sodium pentobarbital. The hair on the back surface was then shaved and disinfected. A full-thickness circular skin defect (10 mm in diameter) was created on the back of the rat using a disposable biopsy punch. The wound was then covered with gauze (negative control group) or yam microgel (30 mg per defect). The rats were euthanized 3, 7, and 14 days after injury for histological analysis. The percentage of wound closure was calculated using ImageJ software according to the following formula:

[0060] Wound closure percentage = (S0-S1) / S0

[0061] Among them, S0 represents the initial wound size, and S1 represents the current wound size. Each test was performed in triplicate.

[0062] In vivo wound adhesion control test

[0063] After anesthesia, the back hair of the rats was shaved and disinfected with iodine and ethanol. Four 2-cm-long incisions were made in each rat. The incisions were then treated with the following four methods: suturing with 4-0 non-absorbable sutures, yam microgel (sterilized under ethylene oxide), cyanoacrylate glue, and hemostasis (as a negative control). The rats were killed on the 1st, 3rd, and 5th days after surgery, and skin samples (3 × 3 cm2) were collected for histological analysis.

[0064] At 7 and 14 days after implantation, tissue samples were fixed in 4% paraformaldehyde, embedded in paraffin, and stained with HE. The sections of each group were subjected to standard procedures, including dewaxing, rehydration, and antigen retrieval. Blocking was performed with 5% BSA for 1 hour at room temperature. Incubation was performed overnight at 4°C with appropriately diluted primary antibodies for specific markers. Rinse with 1x PBS and then treat with HRP-linked secondary antibodies for 1 hour at room temperature. Antigen-antibody complexes were visualized using DAB staining.

[0065] Statistical analysis description:

[0066] Data are presented as mean ± SD. Data analysis was performed using SPSS 20.0 or GraphPad Prism 8 software, and all results were displayed in GraphPad Prism 8. Statistical comparisons were performed using one-way analysis of variance, with significance limited to p < 0.05.

[0067] Statistical significance levels were defined as: *p<0.05, **p<0.05, **p<0.01, ***p<0.001, ****p<0.0001.

[0068] The preparation, characterization and application test results of yam mucus freeze-dried powder and yam microgel are as follows: Figures 1 to 7 shown.

[0069] Depend on Figure 1 It can be seen that: Figure 1 As shown in Figure A, yam mucus freeze-dried powder and yam microgel can be prepared by peeling, grinding, filtering, sieving and freezing. The yam mucus freeze-dried powder is further sieved through a 20-300 mesh sieve. From 20 mesh to 300 mesh, the particle size of the yam powder gradually becomes smaller and finer, see Figure 1 However, the internal structure of yam microgels (fineness 20-300) did not change significantly after hydration (see Figure 1In the rheological characterization, it was observed that the storage modulus of the yam microgel was always greater than the loss modulus at different concentrations, indicating that the microgel maintained a gel state (see Figure 1 In addition, the viscoelasticity of yam microgels increased with the increase of yam microgel concentration (see Figure 1 In addition, mechanical testing found that the shear strength of yam microgels decreased with the decrease of yam powder particle size (see Figure 1 Figures E and F in Figure 3).

[0070] Depend on Figure 2 It can be seen that no obvious L929 cell death was found in the yam microgel treatment groups with different concentrations on the first and third days, see Figure 2 Figure A. Different concentrations of yam microgels had no effect on the proliferation of L929 cells after 1, 3, and 5 days of culture, see Figure 2 Figure B in Figure 2. Figure 2 As shown in Figure C, fibroblasts treated with H2O2 showed strong ROS expression. In contrast, the ROS expression of L929 cells pretreated with yam microgels was significantly reduced, and the inhibitory effect increased with the increase of microgel concentration, especially at 2 mg / mL and 3 mg / mL concentrations. Figure 2 As shown in Figure D, yam microgels at a concentration of 1-3 mg / mL have stronger antioxidant activity. The results of the cell scratch test showed that compared with 0.1-1 mg / mL yam microgels, 2-3 mg / mL yam microgels can significantly accelerate tissue repair (see Figure 2 In addition, the blood compatibility test showed that the blood compatibility of yam microgel extracts at different concentrations was better than that of the positive control (see Figure 2 G and H in the middle). The gelatin sponge was used as a positive control (degraded in 4 weeks). The volume of the implanted yam microgels gradually decreased over time. After 8 weeks of implantation, only a small amount of undegraded yam microgels remained. Figure 2 The I and J diagrams in .

[0071] Depend on Figure 3 It can be seen that: see Figure 3 Figures A to C in the figure, whole blood was added to the yam microgel, gelatin sponge and gauze samples. After sufficient interaction time, the residual blood was removed and the samples were rinsed with distilled water. The red blood cells burst after absorbing water; over time, the yam microgel group became redder and redder than the gelatin sponge and gauze, indicating that the yam microgel can absorb more red blood cells. In particular, 80% of the blood in the 3mg / mL yam microgel treatment group formed blood clots, which was significantly higher than the 2mg / mL (40%) and 1mg / mL (30%) yam hydrogel treatment groups, see Figure 3Figures D and E in Figure 2. Scanning electron microscope images also provide a more intuitive proof that yam microgel can absorb more red blood cells and platelets than gelatin sponge and gauze, see Figure 3 Figure F in .

[0072] Depend on Figure 4 It can be seen that in the rat tail ligation model experiment, the amount of tail bleeding in rats using yam microgel was minimal compared with rats using gelatin sponge or gauze (see Figure 4 The clotting time of yam microgel was the fastest (111.67±5.41 seconds), which was shorter than that of the gelatin group (221.67±10.52 seconds) and the gauze group (265±11.32 seconds) (see Figure 4 The blood loss in the yam microgel group, gelatin group, and gauze group was 0.383±0.048g, 1.293±0.041g, and 1.706±0.034g, respectively, which was less than 2.512±0.043g in the control group (see Figure 2). Figure 4 In rat liver (see Figure 4 G and H in Figure ) and the heart (see Figure 4 Figures I and J in Figure 2 show the interface formed between yam microgel and liver / heart tissue after hemostasis in the perforation bleeding model. The results showed that red blood cells and activated and deformed platelets gathered in large quantities at the interface, indicating that the microgel played an effective role in promoting coagulation and hemostasis. In the gauze group and gelatin sponge group, no tight blood clots or absorbed red blood cells and platelets were found.

[0073] Depend on Figure 5 It can be seen that the wound contraction speed of the yam microgel-treated group was faster than that of the control group. Figure 5 Figures A and B in Figure 1. On days 7 and 14, the wound healing rate of the yam microgel-treated group exceeded that of the control group, see Figure 5 Figure C. In H&E staining on day 7, more newly formed blood vessels were found in the granulation tissue of the yam microgel group compared with the control group. The skin wounds treated with yam microgel had less scar formation 14 days after surgery, see Figure 5 Figure D. The re-epithelialization rate of the yam microgel-treated wounds was consistent with the wound healing rate, see Figure 5 In addition, trichrome staining results confirmed that the angiogenesis of wounds treated with yam microgels was better than that of the control group on the 7th day. After wound healing, the number of blood vessels returned to normal levels on the 14th day, see Figure 5 Figure F. After skin defect occurs, keratinocytes at the wound edge proliferate rapidly and express keratin 6 (K6). Figure 5In Figures G and H, the expression of K6 in the yam microgel-treated group was significantly higher than that in the control group on days 7 and 14. Ki67 is a pan-marker for cell proliferation. The expression of Ki67 was used to detect the proliferation of fibroblasts. Figure 5 In Figures I and J, the Ki67 expression in the yam microgel-treated group was significantly higher than that in the control group on days 7 and 14. CD31 is an indicator of vascularization. The CD31 expression in the yam microgel-treated group was significantly higher than that in the control group on day 7. Figure 5 Figures K and L in Figure 2. Compared with the control group, the α-SMA expression in the yam microgel-treated group was significantly increased on the 7th day, see Figure 5 The M and N graphs in .

[0074] Depend on Figure 6 It can be seen that CD45 is a pan-marker of leukocytes. The expression of CD45 in the wound center treated with yam microgels on days 3 and 7 was significantly lower than that in the control group. Figure 6 Figures A and B in Figure 2. Ly6G is a pan-marker for monocytes, granulocytes, and neutrophils. On day 3, the expression of Ly6G in the wound center of the yam microgel-treated group was lower than that of the control group (see Figure 6 C and D in Figure 2). CD68 is a pan-marker for macrophages, and its total expression in macrophages decreased in the yam hydrogel-treated group compared with the control group. CCR7 and CD206 are markers for M1 and M2 macrophages, respectively, and CCR7 expression in the wound center treated with yam microgels decreased significantly on both days 3 and 7 compared with the control group (see Figure 2). Figure 6 In contrast, the expression of CD206 in the wound center treated with yam microgels was significantly increased compared with the control group on both days 3 and 7 (see Figure 6 The number ratio of M2 macrophages to M1 macrophages in the wound treated with yam microgel was significantly lower than 1 (see Figure 6 The results of Figure 1 indicate that the local inflammatory response is in the pro-regenerative stage and that the yam microgel can promote the polarization of M2 macrophages. In contrast, the control group is in the pro-inflammatory stage (see Figure 6 Figure J in Figure 1).

[0075] Depend on Figure 7It can be seen that compared with 0.5 mg / mL yam microgel, 0.75 mg / mL yam microgel and cyanoacrylate (commercial biological glue), 1 mg / mL yam microgel has the strongest adhesion. The adhesion strength of 1 mg / mL yam microgel is as high as 18.13±1.40 Kpa, while the adhesion strength of cyanoacrylate (commercial biological glue) is only 11.34±0.70 Kpa. In vivo, the wound closure of the skin scratch in the yam microgel treatment group was better than that of the suture group, cyanoacrylate group and control group at each specified time point (see Figure 7 After 7 days of treatment, the skin scratches in the yam microgel-treated group had healed, while the skin scratches in the suture group, cyanoacrylate group, and control group had not healed, especially in the suture group and cyanoacrylate group (see Figure 7 On day 7, the expression of α-SMA in the scratches treated with yam microgels was significantly higher than that in the control group, suture group, and cyanoacrylate group (see Figure 7 C and D in Figure ), which is consistent with the results of wound contraction. On day 7, keratinocytes (K6) in the yam microgel group (see Figure 7 E and F in Figures ) and fibroblasts (Ki67) (see Figure 7 The proliferation of the yam microgel group was significantly higher than that of the control group, suture group, and cyanoacrylate group on day 7. In addition, the expression of CD31 in the scratch area of ​​the yam microgel group was significantly higher than that of the control group, suture group, and cyanoacrylate group on day 7 (see Figure 7 Figure 1 (I and J in Figure 1).

[0076] In addition, the expression of Ly6G in the scratch area of ​​the yam microgel group was reduced on day 7 compared with the control, suture, and cyanoacrylate groups. On day 7, the total number of macrophages expressed in the yam microgel group was lower than that in the control, suture, and cyanoacrylate groups. The expression of CCR7 (M1 macrophages) in the scratch area of ​​the yam microgel was significantly lower than that in the control, suture, and cyanoacrylate groups. In contrast, the expression of CD206 in the scratch area of ​​the yam microgel was significantly higher than that in the control, suture, and cyanoacrylate groups. The ratio of the number of M2 and M1 macrophages in the wound treated with yam microgel was significantly lower than 1, and was lower than that in the control, suture, and cyanoacrylate groups, indicating that the local inflammatory response belongs to the pro-regeneration stage.

[0077] In summary, the yam mucus freeze-dried powder and the hydrogel formed by it can effectively adhere to the wound site, form a protective barrier, stop bleeding and promote tissue regeneration. The yam mucus freeze-dried powder and the hydrogel formed by it have anti-inflammatory effects in the wound repair process.

[0078] It is necessary to point out that the above embodiments are limited to further elaboration and explanation of the technical solution of the present invention, and are not further limitations of the technical solution of the present invention. The method of the present invention is only a preferred implementation scheme, and is not used to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A freeze-dried yam mucus powder, characterized in that: The preparation method of the yam mucus freeze-dried powder comprises the following steps: peeling the yam, squeezing the juice, filtering the yam mucus to obtain the yam mucus, freezing the yam mucus at low temperature, and vacuum freeze-drying the yam mucus to obtain the freeze-dried powder.

2. The yam mucus freeze-dried powder according to claim 1, characterized in that: The low temperature freezing temperature is -80 to -40°C; The vacuum freeze drying temperature is -80 to -40°C.

3. A yam microgel, characterized in that: The yam mucus freeze-dried powder is prepared by hydrating the yam mucus freeze-dried powder according to claim 1 or 2.

4. The yam microgel according to claim 3, characterized in that: The weight ratio of yam mucus freeze-dried powder to water in the hydration process is (10-1):

1.

5. Use of the yam mucus freeze-dried powder according to claim 1 or 2, or the yam microgel according to claim 3 or 4 in the preparation of hemostatic products.

6. The use according to claim 5, characterized in that: The hemostatic product is an in vivo hemostatic product.

7. Use of the yam mucus freeze-dried powder according to claim 1 or 2 and the yam microgel according to claim 3 or 4 in the preparation of products for repairing traumatic injuries.

Citation Information

Cited By

  • Blood coagulation-mediated self-gelling particles as well as preparation method and application thereof

    CN121059871A